Antidiabetic and pancreas-protective potential of Parthenium Hysterophorous (Carrot grass) in Alloxan induced diabetic rabbits: Anti-diabetic Potential of Parthenium hysterophorous - Makhdoom, Munazza; Maqbool, Ayesha; Muhammad, Hafsah; Makhdoom, Sheeba; Ashraf, Hamna; Jawad ul Hasnain, Mirza; Khan, Waseem Ahmed; Irfan, Muhammad (Cellular and Molecular Biology, 2022)
Parthenium hysterophorus has been used to cure cancer, fever, malaria, diarrhea, dysentery, and neurologic disorders. This study evaluates the anti-diabetic effects of methanolic extract of P. hysterophorus (MEPH) in alloxan-induced diabetic rabbits. Twenty-five rabbits were divided into 5groups (N=5). Group-I served as a negative control. Groups II to V were injected with freshly prepared alloxan solution 150 mg/kg intraperitoneally to induce diabetes. Group II till V received following treatments orally: Group II: Alloxan 150 mg/kg alone; group III: Alloxan + MEPH (50 mg/kg); group IV: Alloxan + MEPH (100 mg/kg); group V: Alloxan +Glucophage (62.5 mg/kg), respectively for 10 days. The body weight of all animals was recorded on the 1st, 4th, 7th and 10th days. Short-term (1st, 3rd, 5th and 7th hour) and long-term (4th, 7th and 10th day) hypoglycemic effects were also recorded. All animals were sacrificed on the 10th day to isolate the pancreas for histopathological examination. The results showed that MPEH reduced the blood glucose levels in all the groups of alloxan-induced diabetic rabbits. The histopathological studies depicted that 100 mg/kg of MEPH most effectively repaired alloxan-induced pancreatic damage. The study showed that the MPEH is useful for developing effective phytomedicine to treat diabetes mellitus.